Effect Of Aquatic Plyometric Training Methods And Body Reaction Speed On The Speed Of The Sickle Kick Of The Melati Silat School Sakti City Of Pekalongan - Islam, Syahrizal; Nasuka; Junaidi, Said (Journal of Physical Education and Sports, 2025)
The background of the problem in this study is the low ability of the sickle kick in the Melayi Sakti school of Pekalongan City. This study aims to Analyze the effect of aquatic plyometric training (aquatic plyometric knee tuck jump and aquatic plyometric double leg bound). Analyze the impact of high and low body reaction time on the ability of the sickle kick. Analyze the interaction between aquatic plyometric training and body reaction time on the ability of the sickle kick. This study uses an experimental method with a 2x2 factorial design. The data analysis technique used is Analysis of Variance (ANOVA), with a significance level of 0.005. The population in this study amounted to 28 silat athletes, with a purposive sample technique and specific criteria to be used as samples. The results of the study showed (1). There is a difference in the APT knee tuck jump method and high body reaction speed with a sig value of 0.01 <0.05. (2). There is a difference in the APT knee tuck jump method and low body reaction speed with a sig value of 0.02 <0.05. (3). There is a difference between the APT double leg bound method and high body reaction speed with a sig value of 0.00 < 0.05. (4). There is a difference between the APT double leg bound method and high body reaction speed with a sig value of 0.00 < 0.05. (5). There is an interaction between the aquatic plyometric training method and body reaction speed with a sig value of 0.035 < 0.05. The conclusion is that aquatic plyometric double-leg bound training is more effective for athletes with high body reaction speed to increase the speed of the sickle kick. In contrast, aquatic plyometric double-leg bound training is more suitable for low body reaction speed. Coaches are advised to adjust the training model to the athlete's abilities and provide additional training to increase the speed of the sickle kick.